KEPRIBADIAN, GAYA BERPIKIR, GAYA PEMECAHAN MASALAH, DAN GAYA PENGAMBILAN KEPUTUSAN - Medianta Tarigan; Luluatnul Luluatnul; Tiara Maulida; Anastasia Wulandari (Proyeksi: Jurnal Psikologi, 2019)
This research was conducted to investigate the contributions between personality, thinking style, problem solving style, and decision making style. 301 productive age people (25-44 years old) participated in this study. The researchers used the Myers-Briggs Type Indicator (MBTI) short version, the Gregorc Delineator Style (GDS), VIEW: Assessment of Problem Solving Style, and General Decision Making Style (GDMS). The analysis was performed using the multinomial regression analysis method. The results showed that thinking style is influenced by personality in which several aspects of personality affect several types of thinking styles. Problem solving styles are influenced by thinking styles where several types of thinking styles affect several types of problem solving styles. Decision making style is influenced by thinking style where several types of thinking style affect several types of decision making style. And there is no influence of the problem solving style on the overall decision making style, but several types of problem solving styles affect several types of decision making styles.